Early detection and management strategies for isolated splenic metastasis in cervical cancer: a case report - Zhang, Na (Frontiers in Oncology, 2025)
A 55-year-old woman experienced 2 months of vaginal bleeding after intercourse. After gynecological examination, cervical biopsy, and imaging examinations including magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT), she was diagnosed with stage IIB cervical squamous cell carcinoma, which was associated with human papillomavirus (HPV) infection. The patient subsequently underwent robotic-assisted para-aortic lymphadenectomy, and the pathology results showed no evidence of cancer spread. She completed a treatment plan that included chemoradiotherapy, delivering a total radiation dose of 93.2 Gy along with concurrent cisplatin chemotherapy. Although a post-treatment evaluation indicated a partial remission (PR), follow-up imaging revealed unusual findings in the spleen, which were later confirmed to be metastatic cancer. The patient underwent a laparoscopic splenectomy, and the postoperative pathology confirmed the presence of squamous cell carcinoma metastasis. Genetic testing identified multiple somatic mutations and a high mutational burden in the tumor. After surgery, she received chemotherapy and targeted therapy. At present, her condition is stable, and she has survived for 12 months. This case highlights the complex nature of cervical cancer metastasis and the important role of genetic testing in developing personalized treatment plans.